Transitional justice in the Philippines: A murphyean analysis of the PCHR - Magsaysay, Luke Gerard D. (Animo Repository, 2025)
The Philippines has a long history of human rights atrocities and violations, highlighted by the Philippine Martial Law Era which was declared in 1972. During this time, one of the primary perpetrators of said atrocities was the Marcos administration, which was headed by former Philippine President Ferdinand Marcos Sr. As such, especially during a time of recurrence of these atrocities thanks to the recent expositions regarding the extrajudicial killings during the Duterte administration, it is imperative to analyze why transitional justice measures in the past pertaining to martial law failed. The nonperformance of the measures taken in the past may perhaps be indicative of what can be improved on in order to guarantee the non-recurrence of such atrocious acts. This paper analyzed the functions and powers of the Presidential Committee on Human Rights (PCHR) through a Murphyean lens of what a transitional justice measure ought to be like. Colleen Murphy’s framework is that which revolves around the notion of a just pursuit of societal transformation; that is, the transformation of the ways of interaction among citizens, and between citizens and officials. This paper found section 5d of the PCHR to be problematic, and the entity would have failed regardless of the challenges that impeded its success in the past. Additionally, the paper addressed the said problematic functions and powers of the PCHR, which deemed such to be an unjust TJ response to the atrocities committed during the martial law. Lastly, this paper put forward recommendations for the improvement of the said entity such as the reinstatement of section 4b of the PCHR into the CHR and the omission of section 3.8 of the CHR, which is the same as section 5d of the PCHR’s functions and powers, as the CHR assumed all functions and powers of the PCHR when the latter was abolished due to the new 1987 constitution.